2020
DOI: 10.32749/nucleodoconhecimento.com.br/engenharia-civil/fissuras-em-paredes
|View full text |Cite
|
Sign up to set email alerts
|

Fissuras em paredes de concreto em um conjunto residencial, localizado em São José de Ribamar – Maranhão

Abstract: Este trabalho trata de fissuras em parede de concreto, uma das principais patologias que ocorre em estruturas de concreto. Inicialmente foram levantados dados e informações sobre o conjunto residencial e sobre o sistema construtivo das edificações, realizadas visitas programadas ao local para inspeção visual de forma a analisar os problemas patológicos na estrutura de concreto, seguidas de registros fotográficos e aplicação de questionário com os moradores, onde buscou-se coletar informações sobre o surgiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Revista ALCONPAT, 13 (1), 2023: 112 -130 Evaluation of the effects of thermal variation and shrinkage of concrete in a building with cast-in-place concrete walls Vargas, L. B., Lübeck, A., Santos Neto, A. B. S. 120 reinforcements were shown by Padilha et al (2021) and Lima et al (2020) to allow cracks to appear starting from the corners of openings. Another location affecting stress levels was the intersection of perpendicular walls.…”
Section: Discussion and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Revista ALCONPAT, 13 (1), 2023: 112 -130 Evaluation of the effects of thermal variation and shrinkage of concrete in a building with cast-in-place concrete walls Vargas, L. B., Lübeck, A., Santos Neto, A. B. S. 120 reinforcements were shown by Padilha et al (2021) and Lima et al (2020) to allow cracks to appear starting from the corners of openings. Another location affecting stress levels was the intersection of perpendicular walls.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…This feature imparts safety concern in users and decreases structural durability due to the potential ingress of aggressive agents which can damage concrete and corrode reinforcements (Nakamura and Pinto, 2017). Several studies were conducted to identify the location and frequency of cracks in this type of construction system (Resende et al, 2018;Lima et al, 2020;Netto et al, 2021;Padilha et al, 2021). Results showed that the more susceptible regions for crack formation were edges of doors and windows, edges of walls, along the floor and foundation of large wall panels and on walls and ceiling slabs.…”
Section: Introductionmentioning
confidence: 99%